(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
Anisotropy in rock is among the important parameters that should be considered in studying fracture toughness and fracture mechanisms. Acoustic emission is one of the methods applied to investigate fracture mechanics and how micro- cracks grow in rock samples. This method can help to identify different parts of stress versus strain curves. Using this method, the current research aims to study the effect of anisotropy angles on fracture toughness and fracture mecha- nisms of rock samples. To study the designated parameters, the Cracked Chevron Notched Brazilian Disc (CCNBD) method was selected. Blocks of slate, as an anisotropic rock, were prepared from the Sanandaj-Sirjan zone in Iran. The sample sizes were 54 mm and 74 mm in diameter and 24 mm and 37 mm in thickness, respectively, and their anisotropy angles were 0°, 15°, 30°, 45°, 60°, 75°, and 90°. The tests were carried out in accordance with the method suggested by the International Society for Rock Mechanics (ISRM). Two acoustic sensors were mounted on the specimens to log acoustic waves and determine the acoustic parameters (rise angle and average frequency) for fracture mechanism analysis. About 10 tests were carried out for each angle of anisotropy. Based on the obtained results, it was inferred that anisotropy affects the strength and fracture toughness of rock samples. By increasing the anisotropy angle from 0° to 30°, the strength and fracture toughness decreased. Exceeding this range of angle, with an increase in the anisotropy angle, the strength and fracture toughness increased as well.